High-resolution extreme ultraviolet microscopy : imaging of artificial and biological specimens with laser-driven ultrafast XUV sources /: imaging of artificial and biological specimens with laser-driven ultrafast XUV sources. (2015) - Zürch, Michael Werner
No abstract available